Volume 8B: Heat Transfer and Thermal Engineering 2014
DOI: 10.1115/imece2014-38620
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of Inlet Turbulence on Boundary Layer Development and Momentum/Thermal Wakes for High Pressure Turbine Nozzle and Blade

Abstract: A series of systematic computational studies have been conducted for transonic HPT nozzles and blades to evaluate the impact of free stream turbulence on boundary layer growth and downstream wake mixing. Transition modeling is first compared to measurements for an uncooled nozzle. The computational results are compared against measurements of loading, HTC, and wake predictions. The approach is then applied to a cooled trail-edge nozzle. The added complexity of cooling flow injection at the trail-edge showed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Increasing the inlet turbulence to 20% results in an increased spreading of the wake and mixing losses growing further into the core flow. Kopriva et al (2014) executed the same modeling study at ~0% inlet turbulence for the trailing edge cooled VKI S1N of Kapteijn et al (1996) and found, not surprisingly, a similar trend to the uncooled results as shown in Figure 12. The trailing edge cooling for the cooled VKI vane is a simple slot.…”
Section: Ii4 High Pressure Turbinesupporting
confidence: 78%
See 1 more Smart Citation
“…Increasing the inlet turbulence to 20% results in an increased spreading of the wake and mixing losses growing further into the core flow. Kopriva et al (2014) executed the same modeling study at ~0% inlet turbulence for the trailing edge cooled VKI S1N of Kapteijn et al (1996) and found, not surprisingly, a similar trend to the uncooled results as shown in Figure 12. The trailing edge cooling for the cooled VKI vane is a simple slot.…”
Section: Ii4 High Pressure Turbinesupporting
confidence: 78%
“…As an example, Kopriva et al (2014Kopriva et al ( , 2015 conducted a detailed study of the uncooled VKI S1N of Arts et al (1992) focusing on SST, IDDES, IDDES with a transition model and WALE LES in ANSYS Fluent. Simulations were conducted on unstructured meshes consisting of triangular elements.…”
Section: Ii4 High Pressure Turbinementioning
confidence: 99%
“…Moreover, high pressure turbines operate at both transonic Mach numbers and high Reynolds numbers, which impose great challenges to modern CFD. Conventional RANS and URANS methods have many difficulties in treating unsteady vortical flows in turbines [17][18][19][20] while DNS and LES are too costly [21] especially for high pressure turbines. High pressure turbine cascades had previously not been studied with high-fidelity numerical simulations until the works by Rathakrishnan Bhaskaran [22] with the help of LES.…”
Section: Introductionmentioning
confidence: 99%
“…High pressure turbine cascades had previously not been studied with high-fidelity numerical simulations until the works by Rathakrishnan Bhaskaran [22] with the help of LES. Kopriva et al conducted a detailed study of a high pressure turbine guide vane focusing on the performance comparison of RANS, URANS, hybrid-LES and LES methods in ANSYS Fluent and found that RANS and URANS give worse predictions of the total pressure wake while hybrid-LES and LES produce much better results [20,23]. However, no local loss analysis is carried out in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Denton and Pullan [12] and Zlatinov et al [13] analyzed the local entropy generation rate in turbines with unsteady RANSs. However, Kopriva et al [14,15] found that RANSs have much lower accuracy than large eddy simulations (LESs). Tucker [16,17] indicated that it is particularly difficult to predict unsteady separations in turbines with RANSs.…”
Section: Introductionmentioning
confidence: 99%